PENGARUH MANAJEMEN USAHA DAN ADOPSI TEKNOLOGI TERHADAP KINERJA UMKM DI KABUPATEN SOLOK - Arfimasri Arfimasri; Wahyu Indah Mursalini; Nurhayati Nurhayati; Dorris Yadewani; Yanti Murni; Ratna Rahmadani (STKIP Persada Khatulistiwa Sintang, 2026)
Business management and technology utilization play a crucial role in addressing the gap between the potential role of MSMEs and their actual performance in the region. The purpose of this study was to determine the effect of business management and technology adoption on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Solok Regency. The approach used was quantitative with the causal associative method. Data collection was conducted by distributing questionnaires to the sample. The sample was selected based on a purposive sampling technique totaling 52 MSMEs, using a Likert scale. Data analysis used multiple linear regression statistics, assisted by the SPSS program. The results showed that business management and technology adoption significantly influenced the performance of MSMEs in Solok Regency, both partially and simultaneously. This study suggests the need for a more in-depth study by adding other variables that can influence MSME performance such as innovation, compensation, and policy support. Due to time and scope limitations that cover local sector boundaries, business management and digitalization training are needed to be able to compete globally.